2014
DOI: 10.3389/fnhum.2014.00371
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of a central pattern generator in a reflex-based neuromuscular model

Abstract: Although the concept of central pattern generators (CPGs) controlling locomotion in vertebrates is widely accepted, the presence of specialized CPGs in human locomotion is still a matter of debate. An interesting numerical model developed in the 90s’ demonstrated the important role CPGs could play in human locomotion, both in terms of stability against perturbations, and in terms of speed control. Recently, a reflex-based neuro-musculo-skeletal model has been proposed, showing a level of stability to perturbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
132
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 109 publications
(159 citation statements)
references
References 30 publications
6
132
0
Order By: Relevance
“…Although the spinal architecture responsible for locomotion proposed by Geyer is neuro-physiologically incomplete, the dynamics of the produced gaits are in striking agreement with physiological observations of healthy human walking. This agreement is observed at the muscle level, where similar patterns to those recorded in humans with surface EMG are observed [5] at normal walking speeds.…”
Section: A Neuromuscular Controllersupporting
confidence: 87%
See 4 more Smart Citations
“…Although the spinal architecture responsible for locomotion proposed by Geyer is neuro-physiologically incomplete, the dynamics of the produced gaits are in striking agreement with physiological observations of healthy human walking. This agreement is observed at the muscle level, where similar patterns to those recorded in humans with surface EMG are observed [5] at normal walking speeds.…”
Section: A Neuromuscular Controllersupporting
confidence: 87%
“…The virtual gastrocnemius, a bi-articular muscle, was omitted to avoid a shared control issue, as torques would have been created at both the ankle and absent knee joint. Both the tibialis anterior and soleus control loops were used in pure reflex mode, without the CPG component, as previous studies showed the CPG component is more critical for proximal joints, in particular, the hip joint [5]. The parameters used for the control were the same as presented in [10] except for the soleus muscle resting length, which was decreased to 0.3 cm to account for the difference in morphology between the model and the subjects.…”
Section: A Neuromuscular Controllermentioning
confidence: 99%
See 3 more Smart Citations